Project Management in Digital Disruption: Emergence of Digital Project Management Office - Danko Vukadinovic\'; Robert Fabac (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
This review paper has been prepared to provide an overview of multidisciplinary research that combines recent findings in the fields that support digital transformation development. The potential impact of digital technologies on organizational performance is the leverage that enables changes in common elements of organizational design; such are strategy, structure, processes, or workforce. According to reports by various authors, choosing an approach to digital transformation potentially includes an emphasis on strategy, processes, a structural approach, a project approach, and other performances. Such transformation is often performed through a portfolio of interrelated projects that change the organization. Most contemporary organizations establish a project management office (PMO) as an organizational entity responsible for implementing digital transformation initiatives. In this article, PMO is highlighted as an element of organizational design that promises success in meeting the demands of digital transformation initiatives, such as digital agility or innovation project management, by introducing new digital competencies into its professional domains. Such extensions of PMO domain expertise may lead to the transformation of "traditional" PMOs into digital PMOs. The paper analyses the cases of application of structural elements of digital PMO and their characteristics in three Croatian companies.
Keywords: O32; 330; organizational project management; organizational design; digital transformation; project management office